Family troubles? : exploring changes and challenges in the family lives of children and young people - Ribbens McCarthy, Jane; Hooper, Carol-Ann, 1956-; Gillies, Val (Policy Press, 2013)
This title takes a fresh look at how 'troubles' feature in 'normal' families, and how the 'normal' features in troubled families. In addressing chapter draw on research on a wide range of substantive topics including infant care, sibling conflict, divorce, disability, illness, migration and asylum-seeking, substance misuse, violence, kinship care, and forced marriage.